Externality analysis of oil palm plantation business in Pasangkayu Regency - Khaeruddin Thaha; Andi Herman Jaya; Sri Mulya Palimmi (Institute of Computer Science (IOCS), 2023)
This study aims to determine the positive impact and negative impact on the palm oil plantation business for the community around the palm oil mill company in Bulu Mario Village, Sarudu District. The form of this research is descriptive. The data collection technique used is field research consisting of interviews, questionnaires, and documentation. While the data analysis used is primary data and secondary data collected using descriptive analysis of research that seeks to describe or describe the object under study based on facts in the field. By using key informants and informants as data sources, the data presented uses primary and secondary data through interviews, books, and the internet, then the data analysis technique used in this study is an interactive model qualitative data analysis from Miles Huberman and Saldana. The results showed that the positive impact of this business was felt by the people of Sarudu District. Improving community welfare, increasing income and also the level of education is progressing and developing.